Análisis de vulnerabilidad ante incendios en edificaciones de la zona urbana de la parroquia San Simón, cantón Guaranda, periodo mayo - agosto 2024 - Gaibor Escudero. Patricia Micaela (2025)
The objective of this study is to analyze the fire vulnerability of buildings in the urban area of the San Simón parish, Guaranda canton, period mayo-august 2024. A descriptive quantitative methodology was used, including direct observation and the application of the MESERI method to assess fire risks. The population consisted of 65 buildings, most of which were constructed before 1950 and made with flammable materials such as wood. The collected information was tabulated and analyzed using statistical techniques, allowing the classification of vulnerability levels and identification of high-risk areas. The results showed that 90.8% of the buildings are vulnerable due to their age and lack of fire protection systems. Only 9.2% of the buildings comply with current safety regulations. Additionally, 38.4% of the buildings are in poor or very poor condition, further increasing their susceptibility to fire. Based on these findings, an emergency and contingency plan was designed, including preventive measures, the installation of fire detection systems, community training, and the creation of evacuation routes. It is concluded that the San Simón community faces a high risk of fires, and the implementation of a prevention and response plan is urgently needed to reduce vulnerabilities and improve the safety of its inhabitants.